Knowledge of, and attitudes to giving expressed breastmilk to infants in rural coastal Kenya; focus group discussions of first time mothers and their advisers - Talbert, A; Tsofa, B; Mumbo, E; Berkley, J; Mwangome, M (BioMed Central, 2018)
Background The World Health Organization (WHO)/UNICEF Baby-Friendly Hospital Initiative step number five of the “Ten steps to successful breastfeeding” states “Show mothers how to breastfeed and how to maintain lactation even if they should be separated from their infants.” Urban mothers in Nairobi have low rates of exclusive breastfeeding after returning to work but there are no published data on rural Kenya mothers’ infant feeding practices when working or schooling away from home. Methods We explored knowledge of, and attitudes to, the practice of giving expressed breastmilk in a mixed methods observational study of breastfeeding in rural Kenyan mothers. Fifty mothers with newborns, identified by nurses and community health workers, were asked questions about their experiences of breastfeeding and who they had sought or received advice from on breastfeeding. Focus group discussions, one with community health workers, and four each with mothers and their named advisers were held. Recordings were analyzed using a thematic framework approach. Results The main themes were: the baby’s right to feed from the breast, lack of knowledge about expressing and giving breastmilk, negative attitudes towards expressed breastmilk, and traditional customs for disposing of expressed breast milk. Most participants did not have any experience of giving expressed breastmilk to infants. They described practices of expressing and discarding milk when the mother or baby was ill, to relieve discomfort from engorgement or after the baby had died. Conclusions Feeding expressed breastmilk to infants is a new concept in this context. Promotion of, and training in this practice would help mothers to maintain their milk supply when away from their babies and benefit the infants of working and schoolgirl mothers.